Recommendation: Treatment of clinical long COVID encephalopathies with nasal administered mesenchymal stromal cell extracellular vesicles - Askenase, Philip W. (Frontiers in Nanotechnology, 2022)
We propose therapy with extracellular vesicles (EVs) for dominant central nervous system aspects of chronic clinical Long COVID Syndromes (LCS). These are clinical conditions that have a delayed onset 1-3 months following active SARS-CoV-2 virus infections that cause the resulting acute disease that is called COVID-19. Therapy of LCS will be achieved by direct access to the central nervous system (CNS) mediated by nasal administration of small EVs that are derived from Mesenchymal Stromal Cells (MSC). When administered nasally, these sEVs target CNS microglia and endothelium that are involved in the LCS encephalopathy, as indicated by experimental animal models and human autopsy and spinal fluid studies. Underlying this approach is the discovery that MSC-sEV treatment for healing of neuro injury targets microglia and macrophages that then likely release secondary trophic EVs that affect local capillary endothelial cells to restore vascular integrity. It is postulated that pathways of endothelial and neural pathology in acute SARS-CoV-2 virus infections may carry over to produce underlying vascular and neurological defects mediating LCS that are susceptible to this proposed nasal therapy with MSC-sEVs . Note that MSC-sEVs are healing in diverse diseases and injuries, like Alzheimer’s disease some psychiatric illnesses, with ability to heal active human SARS-CoV-2 virus infections. Further, MSC-sEV induce shift from inflammatory M1-type to healing M2-type microglia. Finally, efficacy of nasal EVs for various CNS abnormalities and use of MSC-sEV systemically for LCS.